The theoretical foundations of the prosecution unit’s specialization (socio-economic nature, benefits and risks) - Єременко , Ю. А. (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2017)
The paper reviews the specialization of prosecution units in Ukraine. The issues of this paper are actual due to the history of the prosecution in this country, which has examples of the formation of various types of specialized prosecution units. Such as (in Ukraine were created): transport prosecutor’s office (including specialized units at the sea, river, railways, air transport), environmental and environmental prosecutor’s office, special procurator’s offices on special (secrete) objects, labor prosecution units, the Pripyat special prosecutor’s office, special prosecution units in the penitentiary institutions, etc. Particular attention is paid to the nature of the specialization in accordance with the principles of management. The author notes that specialization is the characteristic of organizations, either they are profitable or non-profitable, public or private. The goal of their specialization is to increase the efficiency and productivity of the organization. It is confirmed by many well-known scientists who studied the management of enterprises and government agencies. The paper shows the vision of specialization by such world renowned scholars as Adam Smith, Henry Fayol, Max Weber. However, the author emphasizes that the level of specialization should be reasonable. The excess of the required level of specialization negatively effects on the efficiency of work. At the same time, well thought-out specialization directly increases the efficiency of work. The research indicates the internal specialization in the prosecutor’s office in Ukraine, for example prosecutors in the area of drug crimes. At the same time, there is a specialization of entire prosecution units. There are specialized military prosecutors, as well as Specialized Anti-Corruption Prosecutors, in addition to the territorial units in the prosecution system today. The author carried out a research of how the general principles of specialization are implemented in the prosecutors system of Ukraine. Special attention is paid to the advantages and risks of the specialization of the prosecution system. The researcher’s conclusion demonstrates that the risks of forming specialized prosecutor’s offices can be reduced, while many positive features of specialization are worth of their realization.

У статті досліджено природу спеціалізації органів прокуратури, а також здійснено аналіз переваг та ризиків такої спеціалізації.
ТЕОРЕТИЧНІ ОСНОВИ СПЕЦІАЛІЗАЦІЇ ПРОКУРАТУРИ (СОЦІАЛЬНО-ЕКОНОМІЧНА. ПРИРОДА, ПЕРЕВАГИ ТА РИЗИКИ)
Keywords: prosecutor’s office; specialization; specialized agency; organization; efficiency.; прокуратура; спеціалізація; організація; спеціалізована прокуратура; ефективність.